2012
DOI: 10.1536/ihj.53.29
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Triglyceride Concentrations in Lipoproteins as Related to Carotid Intima-Media Thickness

Abstract: SummarySince distinct cholesterol and triglyceride concentrations in major lipoproteins and their subclasses may be related to atherosclerosis, we investigated the relationship of cholesterol and triglyceride concentrations in lipoprotein subclasses and the severity of carotid intima-media thickness (IMT), a surrogate marker of subclinical atherosclerosis. We studied 116 apparently healthy Japanese men (53 ± 9 years) without a history of cardiovascular diseases who were not taking any medication. Carotid IMT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Although other studies showed an association between grades of NAFLD and CRP levels, in this study this correlation was not found [18,19]. Moreover, 2-h postload plasma glucose levels, within normal glucose tolerance, and LDL-cholesterol are associated with carotid intima-media thickness, a marker of early atherosclerosis [20,21].…”
Section: Discussioncontrasting
confidence: 58%
“…Although other studies showed an association between grades of NAFLD and CRP levels, in this study this correlation was not found [18,19]. Moreover, 2-h postload plasma glucose levels, within normal glucose tolerance, and LDL-cholesterol are associated with carotid intima-media thickness, a marker of early atherosclerosis [20,21].…”
Section: Discussioncontrasting
confidence: 58%
“…20) Saiki, et al 21) reported that CAVI increased with an increase in the number of risk factors for metabolic syndrome. Moreover, CAVI has been shown to decrease following various interventions to reduce coronary risks, including some medications for metabolic disorders, 22,23) weight reduction, 24) and smoking cessation. 25) Therefore, CAVI is considered to be a good physiological surrogate marker for vascular injury because it can detect reversible vascular disorders, and is useful to assess the effect of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also some studies that showed that a higher BMI was not associated with worse outcomes of AMI patients after PCI, which was called obesity paradox [25,26]. Whether the obesity paradox exists in Asian or Chinese patients still remains controversial [27]. We analyzed these studies that are inconsistent with our results, and Figure 2: Association between BMI and readmission of AMI.…”
Section: Discussionmentioning
confidence: 64%